A simplified multi‐objective optimization‐based direct finite‐control‐set model predictive control for active front‐end rectifiers with fast dynamic response. Issue 2 (24th August 2017) - Liu, Xing; Wang, Dan; Peng, Zhouhua
Abstract : In this paper, a simplified, multi‐objective, optimization‐based, direct finite‐control‐set model predictive control method is proposed for active front‐end rectifiers. Specifically, the proposed method replaces a cost function to combine a simplified computational method and multi‐objective optimization strategy based on average ranking. The process of selection of the desired voltage vector is optimized by using a sector distribution method. Meanwhile, the proposed method can achieve flexible control of powers without overshoot by applying dynamic references through mathematical deduction. The advantages of the proposed method can be summarized as follows: First, the proposed algorithm avoids the tuning of the weighting factors without affecting the control performance. Second, due to the fact that the proposed strategy avoids the use of an external proportional‐integral controller, fast dynamic response can be obtained. Third, since the proposed strategy avoids exhaustive explorations for testing all feasible voltage vectors, the optimizing efficiency can be improved. Simulation results are presented to demonstrate the efficacy of the proposed method. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.